2011
DOI: 10.1128/jvi.01760-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations in a Tissue Culture-Adapted Hepatitis C Virus Strain Improve Infectious-Virus Stability and Markedly Enhance Infection Kinetics

Abstract: Hepatitis C virus (HCV) establishes persistent infections and leads to chronic liver disease. It only recently became possible to study the entire HCV life cycle due to the ability of a unique cloned patient isolate (JFH-1) to produce infectious particles in tissue culture. However, despite efficient RNA replication, yields of infectious virus particles remain modest. This presents a challenge for large-scale tissue culture efforts, such as inhibitor screening. Starting with a J6/JFH-1 chimeric virus, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 46 publications
5
47
0
Order By: Relevance
“…3). Previous studies have described adaptive mutations throughout the genome when passaging JFH-1-derived viruses (68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Specifically, N34D in E2 results in the loss of a well-characterized N-glycosylation site (E2N1) that has been linked to modulation of entry functions of HCV envelope proteins without interfering with viral morphogenesis (78).…”
Section: Discussionmentioning
confidence: 99%
“…3). Previous studies have described adaptive mutations throughout the genome when passaging JFH-1-derived viruses (68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Specifically, N34D in E2 results in the loss of a well-characterized N-glycosylation site (E2N1) that has been linked to modulation of entry functions of HCV envelope proteins without interfering with viral morphogenesis (78).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of replication, the NS3-5B region is sufficient to sustain viral RNA synthesis (12), and each of the proteins derived from this polyprotein is also known to contribute to virus production (30,(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)(47)(48). Our previous studies have shown that the kinetics of cleavage at boundaries between the NS proteins plays a critical role in reg- , and G1911A refer to the NS3-5B polyprotein expressed in the second cistron for each construct; wt denotes wt versions of NS5A and NS4B, S2208I indicates the mutation in NS5A, and G1911A denotes the mutation in NS4B.…”
Section: Discussionmentioning
confidence: 99%
“…Cell imaging shows that the RC lies proximal to sites where virus assembly probably occurs, since double-stranded RNA and MAF colocalize with envelope proteins and core-coated lipid droplets (30)(31)(32); the latter structures are thought to represent both a repository and a transitionary step in the maturation of core from a monomeric protein to a capsid shell (33,34). In addition, it has been conclusively demonstrated that mutations in the NS proteins can affect the efficiency of virus particle production independently of any effect that these changes may have on RNA replication (30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Such data illustrate the tight link between viral RNA replication and virion assembly.…”
mentioning
confidence: 99%
“…NS3-NS5B are essential for HCV RNA synthesis (25) and localize to replication complexes (RCs) embedded within cellular endoplasmic reticulum (ER) membranes (8,13,41,48). However, many of the nonstructural proteins are also engaged in the generation of infectious virions, with reports of NS3 (14,26,53), NS4A (38), NS4B (17,40), and NS5A (3,27,31,50,51) being essential for, or at least contributing to, this process. It is therefore becoming apparent that the assembly of infectious virus particles is a complex, multistep mechanism involving the majority of the HCV-encoded proteins.…”
mentioning
confidence: 99%